2016
DOI: 10.1038/cddiscovery.2016.18
|View full text |Cite
|
Sign up to set email alerts
|

Xenon-mediated neuroprotection in response to sustained, low-level excitotoxic stress

Abstract: Noble gases such as xenon and argon have been reported to provide neuroprotection against acute brain ischemic/anoxic injuries. Herein, we wished to evaluate the protective potential of these two gases under conditions relevant to the pathogenesis of chronic neurodegenerative disorders. For that, we established cultures of neurons typically affected in Alzheimer's disease (AD) pathology, that is, cortical neurons and basal forebrain cholinergic neurons and exposed them to L-trans-pyrrolidine-2,4-dicarboxylic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 65 publications
0
31
0
1
Order By: Relevance
“…The technical set‐up used for the supply of the pre‐defined gas atmospheres (20% O 2 , 5% CO 2 and 75% of the test gas) has been previously described in detail (Lavaur et al . ). The incubation chambers were maintained at 37°C in a conventional cell culture incubator for time periods indicated in the manuscript.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…The technical set‐up used for the supply of the pre‐defined gas atmospheres (20% O 2 , 5% CO 2 and 75% of the test gas) has been previously described in detail (Lavaur et al . ). The incubation chambers were maintained at 37°C in a conventional cell culture incubator for time periods indicated in the manuscript.…”
Section: Methodsmentioning
confidence: 97%
“…In particular, we showed for the first time that a sustained exposure to xenon provides neuronal rescue in culture settings that are relevant to the pathogenesis of Alzheimer's disease (Lavaur et al . ). Interestingly, we found that xenon also worked as a trophic factor toward basal forebrain cholinergic neurons, a neuronal population at risk in this disorder (Lavaur et al .…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Consistent with this view, DA cell death induced by PDC was also efficiently reduced by antagonizing NMDA receptors with memantine, in cultures maintained under 75% nitrogen. Note that the site to which xenon binds on NMDA receptors appears distinct from that of memantine (Kotermanski and Johnson 2009;Liu et al 2010) and unrelated to the glycine binding site of the receptor in the present setting (Lavaur et al 2016a). Indeed, glycine is inherently present in Neurobasal culture medium at a concentration of 400 μM, which is sufficient to saturate the NMDA receptor glycine-binding site (Dickinson et al 2007).…”
Section: Discussionmentioning
confidence: 76%
“…Specific gas concentrations were produced with a gas mixing system (GasMix, Alytech, Juvisy/Orge, France) supplied by compressed gas cylinders of individual pure gases. The description of the technical procedure used to fill up incubation chambers with gas atmospheres has been previously described in detail (Lavaur et al 2016a(Lavaur et al , 2017. The control cell culture atmosphere contained 20% O 2 , 5% CO 2 and 75% N 2 and test atmospheres adequate percentages of noble gases in replacement of an equivalent amount of nitrogen.…”
Section: Exposure To Gas Atmospheresmentioning
confidence: 99%